2019
DOI: 10.1007/s00220-019-03516-2
|View full text |Cite
|
Sign up to set email alerts
|

Entropy of Physical Measures for $$C^\infty $$ Dynamical Systems

Abstract: For a C ∞ map on a compact manifold we prove that for a Lebesgue randomly picked point x there is an empirical measure from x with entropy larger than or equal to the sum of positive Lyapunov exponents at x. This contrasts with the well-known Ruelle inequality. As a consequence we give some refinement of Tsujii's work [22] relating physical and Sinai-Ruelle-Bowen measures.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In this section we use tools introduced firstly in [14] to bound the distorsion of unstable manifolds. As these manifolds are one-dimensional, the reparametrizations in Yomdin's theory are just affine.…”
Section: Proof Of Propositionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this section we use tools introduced firstly in [14] to bound the distorsion of unstable manifolds. As these manifolds are one-dimensional, the reparametrizations in Yomdin's theory are just affine.…”
Section: Proof Of Propositionmentioning
confidence: 99%
“…As these manifolds are one-dimensional, the reparametrizations in Yomdin's theory are just affine. In fact we can in this case completely avoid the use of the classical Yomdin's Reparametrization Lemma by applying the Landau-Kolmogorov inequality as in [14]. 5.1.…”
Section: Proof Of Propositionmentioning
confidence: 99%
See 2 more Smart Citations
“…• Also in C ∞ setting, Burguet [4] has shown that for Lebesgue almost every point x ∈ M , there is some invariant probability measure in the limit set of { 1 n n−1 j=0 δ f j (x) } n∈N with entropy larger than (or equal to) the volume growth rate on the direction with positive upper Lyapunov exponents. He also gave some counterexample to show that it is not true if the system only has finite regularity.…”
Section: Introductionmentioning
confidence: 99%